Implementing IYCF counseling centers in Bihar - Dar, Shivani; Jha, Rakesh; Sinha, Sudhir; Singh, Banke Bihari; Kumar, Gourav (International Food Policy Research Institute, 2015)
Bihar is greatly challenged by a low rate of recommended infant and young child feeding (IYCF) practices. For example, only 30 percent of newborns are breastfed within one hour, and only 29 percent of children are exclusively breastfed for the first six months in Bihar (Government of India 2014). Poor breastfeeding practices alone lead to 800,000 child deaths each year in Bihar— almost 12 percent of all child deaths in the state (Aga Khan 2015). Optimal IYCF practices are urgently needed in the health facilities and at the community level.